In silico study of Rumput Fatimah (Anastatica hierochuntica L.) estrogenic activities and its potential as phytoestrogens - Heny Astutik (Association of Pharmaceutical Innovators, 2019)
Background: Rumput fatimah (Anastatica hierochuntica L.) is a desert plant known as a traditional Indonesian medicine to help the childbirth process become more comfortable; however, there is no scientific evidence to support this. In silico tests were performed using computer simulation methods to initiate the discovery of new drug. Objectives: This study aimed to determine the prediction of estrogenic activity compounds in rumput fatimah (Anastatica hierochuntica L.) and its potential as a phytoestrogen with target agonists to the estrogen receptor. Methods: Phytochemical tests of rumput fatimah (Anastatica hierochuntica L.) extract using the liquid chromatography mass spectrometry method (LCMS), and the activities prediction of Anastatica hierochuntica L. was conducted using PASS SERVER In silico studies were done using PASS server to predict estrogenic activity and molecular docking by utilizing the role of computational chemistry and the ACD/I-Lab program online. Result: In this study, it was found that active compounds in rumput fatimah had low activity against estrogen receptor agonists because the average value of activity obtained was low (<0,3). The results of molecular docking using the PyRx program showed that isopimaric acid was a compound that has a binding affinity value close to that of estradiol, so isopimaric acid is predicted to be a phytoestrogen. Conclusion: Isopimaric acid is one of the estrogen receptor ligands found in rumput fatimah (Anastatica hierochuntica L.) which provided the greatest affinity and good potential as phytoestrogens.